Exergetic analysis of a natural gas steam gas reformer - Sosa, María Isabel (Revista Ciências Exatas, 2009)
The objective of this work is to present results of the exergetic analysis. In previous investigations, we presented a model of a natural gas steam reformer, analyzed from a thermal point of view using the program SIMUREFGN and economically by means of HIDROCOS. The reformer's thermodynamic efficiency as a function of operative conditions evaluates its thermal feasibility and the exergetic efficiency its thermodynamic quality. Hydrogen generation cost fluctuates depending on several factors taken into account, such as hours of operation, fuel used to generate steam in the steam generator. The exergetic analysis allows a better way to optimization the system. Reforming process depends on temperature and pressure. An exergetic analysis allows an optimization of the reforming process and a minimization of operating costs. Thermal dependence of irreversibility appears to be not significant; on the other hand pressure has an important effect. A lower irreversibility value comes out, operating at atmospheric pressure and temperature ranging between 600º-800ºC. An exergetic flow diagram allows the calculation of exergetic efficiencies optimize the reformer operation. Conclusions are presented.